PENGARUH VARIASI WAKTU TINGGAL TERHADAP KADAR BOD, COD, DAN TSS PADA PENGOLAHAN LINDI TPA BUKIT PINANG SAMARINDA MENGGUNAKAN SISTEM AERASI BERTINGKAT DAN SEDIMENTASI - Sarwono, Edhi; Azis, Wahyu Arindra; Widarti, Budi Nining (Jurnal Teknologi Lingkungan UNMUL, 2017)
AbstractLeachate contains organic and anorganic materials that are harmful to surface water so that need a treatment to reduce water pollute in environment. Leachate can be treated with aerobic processes using aeration and sedimentation processes to reduce levels of BOD, COD and TSS. The Purposes of this research was to determine the effect of detention time variation on the concentration of BOD, COD, and TSS using multilevel system of aeration and sedimentation. The method used in this research was a batch reactor system using a multilevel system of aeration and sedimentation. The research was conducted during one month using a variation of detention time 4 hours, 6 hours and 8 hours. In the treatment process using some reactor wastewater treatment plants obtained optimum residence time in the aeration reactor unit is 8 hours. From the results of the optimum results obtained by the BOD levels reduced as much as 91.3% from the initial 731.92 mg / L to 63.65 mg / L, COD fell as much as 39.4% from the initial 1871.42 mg / L to 1133.44 mg / L and TSS levels fell as much as 95.1% of the initial state 395, 8 mg / L to 50.4 mg / L.